Peningkatan Kompetensi Tenaga Kependidikan Melalui Workshop Pengelolaan Arsip Elektronik di SMA Negeri 1 Kalasan - Kustitik, Kustitik; Dimas Ellix , Ramadhan; Dwi Elisa, Zunita; Nurul Baiti, Muharrimah; Silfa Amalia, Ikrimah; Alfian Wino, Syawal; Ahmad, Ridho; Novia, Puspitasari; Froys Wiras, Fairyo; Yohanes, Parjoko; et al. (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2024)
This activity aims to provide new insights and skills to educational staff in the effective and efficient management of electronic records, in line with the needs of the digital era. The target group was 16 educational staff at SMA Negeri 1 Kalasan. The activity was implemented in three stages: a material session, a discussion session, and a simulation. The material presented covered: the definition of digital archives, the urgency of archive management, digital archive management, and the benefits of digital archive management. The results of the activity showed significant improvements in both understanding and skills. Participants stated that the material presented was very useful in supporting their work and assignments at school.